1988
DOI: 10.1038/bjc.1988.301
|View full text |Cite
|
Sign up to set email alerts
|

Cinnarizine and flunarizine as radiation sensitisers in two murine tumours

Abstract: Summary The effect of the calcium antagonists, cinnarizine and flunarizine on the radiation sensitivity of two murine tumours, RIF-1 and SCCVII/St was investigated. Initial experiments giving the compounds at 50mgkg-1 i.p. indicated that cinnarizine had no effect on cell survival after 20Gy of X-rays in the RIF-1 sarcoma and only a small effect in the SCCVII/St carcinoma. However, flunarizine produced a small radiosensitisation in the RIF-1 tumour and a substantial sensitisation in the SCCVII/St tumour. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…The effect is not so pronounced as that reported for the cinnarizine and flunarizine radiosensitisation in normal mice (Wood & Hirst, 1988). The reason for this is not clear but may be related to the fact that in this study cinnarizine and flunarizine are being given to anaemic mice.…”
Section: Discessionmentioning
confidence: 56%
See 3 more Smart Citations
“…The effect is not so pronounced as that reported for the cinnarizine and flunarizine radiosensitisation in normal mice (Wood & Hirst, 1988). The reason for this is not clear but may be related to the fact that in this study cinnarizine and flunarizine are being given to anaemic mice.…”
Section: Discessionmentioning
confidence: 56%
“…The time course for the effect of erythrocyte transfusion on tumour response to 20 Gy X-rays in anaemic mice has been reproduced in Figure (Wood & Hirst, 1988) and are reproduced with permission. In both cases radiosensitisation occurred, but the time course and the size of the effect were different for the two tumours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flunarizine (E-1 -[bis(4-fluorophenyl)methyl]-4-(3-phenyl-2-propenyl)piperazine dihydrochloride) is a WHO class IV calcium-entry blocking agent which enhances radiosensitivity in vivo in animal models (Wood & Hirst, 1988). Numerous studies have demonstrated that the drug significantly improved blood flow and oxygenation in the hypoxic regions of tumours implanted experimentally in animals (Kaelin et al, 1984;Vaupel & Menke, 1987;Fenton & Sutherland, 1992).…”
mentioning
confidence: 99%